Central bank performance under inflation targeting - Marc-André Gosselin (Bank of Canada, 2007)
The inflation targeting (IT) regime is 17 years old. With practice of IT now in more than 21 countries, there is enough evidence gathered to take stock of the IT experience. In this paper, we analyze the inflation record of IT central banks. We extend the work of Albagli and Schmidt-Hebbel (2004) by looking at a broad range of factors that can influence inflation target deviations and by identifying the empirical determinants of successful monetary policy under IT. We find that part of the cross-country and time variation in inflation deviations from targets can be explained by exchange rate movements, fiscal deficits, and differences in financial sector development. With respect to the components of the IT framework, we find that a higher inflation target and a larger inflation control range are associated with more variable inflation (and output) outcomes. Although the literature tends to suggest that greater central bank transparency is desirable, our findings imply that transparency might be associated with less satisfactory inflation performance. Interestingly, central banks using economic models do a better job of stabilizing inflation around the target and output around trend.
Keywords: E31; E52; E58; 330; Central bank research; Inflation targets; Monetary policy framework; Zentralbank; Inflation Targeting; Geldpolitik; Vergleich; Welt